2004
DOI: 10.1111/j.1348-0421.2004.tb03476.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibility to Tetracycline and Fluoroquinolones of Japanese Isolates of Coxiella burnetii

Abstract: Coxiella burnetii is the agent of the worldwide zoonosis, Q fever. The in vitro susceptibility to tetracycline and fluoroquinolones of Japanese isolates of C. burnetii was evaluated for the first time. The MICs against Japanese isolates were almost the same as the MICs against the foreign reference isolates. The results suggest that the common antibiotics therapy for Q fever used in other countries is also effective for Japanese Q fever patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…It was then applied in another study from our team, which confirmed its excellent reproducibility for MIC determination (20). In recent years, both the IFA and qPCR tests targeting com1 or apoB have been used for C. burnetii AST in various eukaryotic cell lines (21)(22)(23)(24). We recently developed a new method using flow cytometry and specific immunofluorescent probes.…”
Section: Search Strategymentioning
confidence: 79%
“…It was then applied in another study from our team, which confirmed its excellent reproducibility for MIC determination (20). In recent years, both the IFA and qPCR tests targeting com1 or apoB have been used for C. burnetii AST in various eukaryotic cell lines (21)(22)(23)(24). We recently developed a new method using flow cytometry and specific immunofluorescent probes.…”
Section: Search Strategymentioning
confidence: 79%
“…At the concentrations used (for tigecycline, 0.03 g/ml to 8 g/ml, and for the rest of the antibiotics, 0.25 g/ml to 16 g/ml), the solvents were nontoxic to normal or infected Vero cells. The bacteriostatic and bactericidal effects of antibiotics against C. burnetii were tested by a shell vial assay (1,4,5,6,9,13,16,21). For this purpose, Vero cell monolayers cultured in shell vials were infected with 10-fold serial dilutions of a C. burnetii inoculum to determine the inoculum dilution that resulted in 50% infected Vero cells after 6 days of incubation.…”
mentioning
confidence: 99%
“…Furthermore, a combination of doxycycline with the lysosomotropic agent chloroquine displayed bactericidal activity in vitro, but no definitive clinical data were presented (8,17,18). Quinolones also exhibit in vitro activities against rickettsiae and have produced encouraging clinical results in Q fever patients (1,6,21). Previous work with other bacteria demonstrated that tigecycline specifically inhibits protein synthesis in an in vitro assay system containing the bacterial enzymes required for transcription and translation.…”
mentioning
confidence: 99%
“…Studies suggest doxycycline, gatifloxacin, levofloxacin, moxifloxacin, and ciprofloxacin are the most effective antibiotics against C. burnetii isolates [14]. The patient initially received moxifloxacin and levofloxacin, but the response was unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%